Synthesis and Characterization of Diazenyl-1,3-diphenylpropane-1,3-dione and 5-[Hydroxy(phenyl)methyl]-4-phenylpyrimidine Derivatives - Önal*, Zülbiye; Özalp, Ayhan; Özer Ilhan, Ilhan; Aslan, Güzin (Asian Journal of Chemistry, 2014)
Various novel diazenyl-1,3-diphenylpropane-1,3-dione derivatives (2a-f) were prepared by the condensation of the diazonium salts of N-aminopyrimidine derivatives with b-diketones. Also, a series of novel 5-[hydroxy(phenyl)methyl]-4-phenylpyrimidine derivatives (3a-f) were synthesized from the reduction reactions of N-aminopyrimidine derivatives with NaBH4. The structures of all the new synthesized compounds were characterized by the 13C-NMR, 1H-NMR and IR spectroscopic data and elemental analysis.